Penerapan E-Commerce untuk Meningkatkan Penjualan Sepatu pada Toko Garasi Spokat - Busthomi Algifari; Atik Ariesta (Ikatan Ahli Informatika Indonesia, 2020)
Garasi Spokat is a shop that sells shoes with original and good quality. Garasi Spokat developed to meet customers' needs. Business sales at the Garasi Spokat are still less effective, customers must come to the store to buy and find out information about the products. Media marketing only through banners in stores, making the scope of sales less extensive. This research aims to build an E-Commerce Website using Wordpress Content Management System (CMS). Business Model Canvas (BMC) methods used to clarify elements that can help achieve business goals, and Unified Modeling Language (UML) used to analyze system processes. The results of this study are e-commerce websites that help customers to find out information on products online that can be access anywhere and anytime, to increase sales and expand the scope of sales.